Correlation of new generation of anti-cyclic citrullinated peptide antibodies in combination with rheumatoid factor with diagnosis, severity, functional status and prognosis - Azalan, Maryam Syahidah (2021)
Rheumatoid arthritis (RA) is an autoimmune disease which lead to progressive joint damage and affects patient’s quality of life. Since rheumatoid factor (RF) has limited diagnostic performance, new generation of anti-cyclic citrullinated peptide (anti-CCP) antibodies were then introduced. The combination of RF and anti-CCP antibodies is ultimately important for diagnosis, prognosis, and clinical management of RA disease. This study aims to compare serum RF, anti-CCP2 IgG, anti-CCP2 IgA and anti-CCP3.1 IgG/IgA antibodies status in RA patients and healthy controls. The association between these serological markers and disease severity, as well as factors associated with functional status of RA patients were also evaluated. This cross-sectional study was conducted among 46 RA patients and 40 healthy controls in Rheumatology Clinic, Hospital USM. Self-administered questionnaires containing three parts; sociodemographic, clinical characteristics, and modified Health Assessment Questionnaire (mHAQ) form were used. Then, disease activity score (DAS28) of RA patients were assessed and five millilitres of blood was withdrawn of all subjects. RF was analysed using Direct Latex, whereas anti-CCP2 IgG, anti-CCP2 IgA and anti-CCP3.1 IgG/IgA antibodies were assayed using enzyme linked immunosorbent assay (ELISA). The data were analysed using SPSS version 26.0 with the p value < 0.05 was considered significant. The association of DAS28 with serological markers were analysed using independent sample t-test while factors associated with mHAQ were analysed using multiple linear regression (MLR). Majority of RA patients had positive status of serum RF (78.3%), anti-CCP2 IgG (63.0%) and anti-CCP3.1 IgG/IgA (63.0%). Significant differences were found in RF (p<0.0001), anti-CCP2 IgG (p<0.0001), anti-CCP2 IgA (p<0.0001) and anti-CCP3.1 IgG/IgA (p<0.0001) antibodies between RA and control groups. RA patients had moderate disease severity based on the DAS28 score, while their mHAQ score showed mild functional status with mean score of 3.52 (SD 1.13) and 0.47 (SD 0.61) respectively. No significant association was found between disease severity with all serological markers. Significant association were found between pain score (p <0.0001) and anti-CCP2 IgG antibody status (p =0.049) with functional status of RA. No significant association between RF with DAS28 and mHAQ score. Positive status of RF, anti-CCP2 IgG, and anti-CCP3.1 IgG/IgA antibodies in majority of RA patients indicates the significance of these serological markers in diagnosis and prognosis of RA. Anti-CCP2 IgG antibody can be considered as the best diagnostic tool compared to other serological markers since it has significant association with the functional status. Future studies were important to obtain more understanding regarding the role of new generation anti-CCP antibodies in diagnosis and pathogenesis of RA.